The hypothesis of non-African origin of human immunodeficiency virus type 1 - V. P. Sergiev (Журнал инфектологии, 2014)
Longitudinal co-evolution of human beings and pathogens resulted in polymorphism of Homo sapiens. CCR5Δ32 HIV-resistance allele is the exception to the rules. Recent origin of HIV-1 in Africa contradicted with the appearance of CCR5Δ32 allele in Northern Europe in previous ages.The author proposed non-contradictory theory of primary appearance of ancient HIV-1 in the Northern Europe 5-7 thousand years ago. The primary epidemics of HIV-infection had been stopped by the appearance of CCR5Δ32 mutation among the affected population. Re-emergence of HIV-1 nowadays resulted by the penetration of hibernated HIV-1 into population of drug addicts and homosexual men.